Efficacy of Zingibain phyto-protease on growth performance, litter quality and gut microbiota in broilers fed high animal protein concentrates - Muhammad Shahkar Uzair; Asad Sultan; Ziaul Islam; Muqadar Shah; Muhammad Tahir; Shabana Naz; Abdulwahed Fahad Alrefaei; Sheikh Adil; Naseer Khan Momand; Rifat Ullah Khan (Italian Journal of Animal Science)
This study examined the effects of dietary supplementation with animal protein concentrate (APC) and ginger phyto-protease (GPZ) on growth performance, carcase yield, litter quality and gut microbiota in broiler chicks over a 35–day period. A total of 700-day-old chicks were divided into give groups with five replicates as follow: control (standard diet), diet with 4% APC, diet with 6% APC, diet with 4% APC + GPZ at 0.02% and diet with 6% APC + GPZ at 0.02%. The results showed that GPZ supplementation improved body weight gain (BWG) and feed conversion ratio (FCR) in diets containing APC. Carcase yield analysis revealed that diet with 4% APC + GPZ, and diet with 6% APC + GPZ had the highest yields (p < 0.01). Immune organ weights of spleen and bursa of fabricius were significantly increased in groups having 4 and 6% APC with GPZ (p = 0.02). Additionally, gut microbiota analysis indicated that treatments with GPZ effectively reduced harmful bacteria (Clostridium perfringens, Escherichia coli, and Salmonella) while promoting the growth of beneficial Lactobacillus. Overall, GPZ supplementation at the level of 0.02% in 4% APC added diet proved more effective in improving feed conversion, reducing harmful bacteria, and promoting the growth of beneficial gut microbiota.